New synonyms of Philonotis polymorpha (Bartramiaceae, Bryophyta) from Southern South America - Jimenez, Maria Soledad (2016)
Philonotis polymorpha is a medium sized plant, yellowish-green to reddish-brown below, commonly found growing sterile on wet rocks or soil in forests, near rivers and waterfalls. Diagnostic characters of this species are the dimorphic leaves, ovate to oblong-lanceolate, the abruptly short-acuminate apex, margins plane, serrate at the apex, entire at the base, the excurrent, robust and well defined costae, ending in a mucro, and the papillae projecting at proximal angles of laminal cells. During the development of this work, we have examined type specimens of several names within the genus. As result, four new synonyms are proposed for P. polymorpha, and three lectotypes are designated.